Transfer of Perceptual Learning From Local Stereopsis to Global Stereopsis in Adults With Amblyopia: A Preliminary Study - Chopin, Adrien; Silver, Michael A.; Sheynin, Yasha; Ding, Jian; Levi, Dennis Michael (Frontiers in Neuroscience, 2021)
It has long been debated whether the analysis of global and local stereoscopic depth is performed by one or separate systems. Global stereopsis requires the visual system to solve a complex binocular matching problem to obtain a coherent percept of depth. In contrast, local stereopsis requires only a simple matching of similar image features. In this case series, we recruited 5 adults with amblyopia who lacked global stereopsis and trained them on a computerized local-disparity stereoscopic depth task for an average of 12 hours. Three out of five (60%) participants recovered fine global stereoscopic vision. Those who recovered tended to start the training with better initial performance on the local-disparity task, to have less severe amblyopia, and to improve more on the local-disparity training task. The transfer of learning from local stereopsis to global stereopsis is compatible with an interacting two-stage model.